YOUTUBE VIDEOS FOR IMPROVING SPEAKING SKILLS: THE BENEFITS AND CHALLENGES ACCORDING TO RECENT RESEARCH IN EFL CONTEXT - Purwanti, Ni Komang Ratna; Suwastini, Ni Komang Arie; Adnyani, Ni Luh Putu Sri; Kultsum, Ummi (Universitas Pendidikan Ganesha, 2022)
The improvement of students' speaking skills requires students to communicate with the interlocutors interactively. In the context of globalization, social media have become a medium of communication that can enhance students' speaking skills. The present study investigated what previous research had concluded on the use of YouTube videos to enhance the development of students' speaking skills by adapting George's (2008) model of library research into a qualitative design. The study revealed that YouTube videos had been proven to give better exposure to the students' speaking aspects like pronunciation, structure, vocabulary, intonation, grammar, and fluency. However, the use of YouTube videos also poses challenges, such as unstable internet connection, loss of interaction with peers and teachers, low comprehension of the videos, unsuitable length of videos, students’ low readiness and autonomy, and discrepancy between the videos and the language learning goals. These findings imply that while YouTube videos can be helpful learning tools, the right strategies need to cope with the challenges.